Meningkatkan Hasil Belajar Dan Keterampilan Berpikir Kritis Menggunakan PjBL Dan Talking Stick - Shella Wati; Mahmuddin (CV. ITTC INDONESIA, 2023)
This study uses a combination of PjBL and Talking Stick models in learning activities to explain instructor activities, analyze student actions, assess critical thinking skills, and measure student learning outcomes. Classroom action research (CAR), which uses a qualitative methodology, falls into this category. Ten fifth graders from SDN Tanipah 1 became the subject of research during the 2022–2023 school year. Student learning outcomes in general get a score of 90%. Based on the reseerch findings, it can be said that using the PjBL and Talking Stick models can help teacher-led learning run smoothly, and individual student learning outcomes and individual student activities can obtain a score of 90% with the